2007
DOI: 10.1242/jcs.03372
|View full text |Cite
|
Sign up to set email alerts
|

TACE release of TNF-α mediates mechanotransduction-induced activation of p38 MAPK and myogenesis

Abstract: manner. Stretch stimulated the cleavage activity of TACE. Conversely, TACE inhibitor TAPI or TACE siRNA abolished stretch activation of p38. In addition, conditioned medium from stretched myoblast cultures activated p38 in unstretched myoblasts, which required TACE activity in the donor myoblasts, and TNF-␣ receptors in the recipient myoblasts. These results indicate that posttranscriptional activation of TACE mediates the mechanotransduction that activates p38-dependent myogenesis via the release of TNF-␣.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
98
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(110 citation statements)
references
References 84 publications
(113 reference statements)
12
98
0
Order By: Relevance
“…1D). Consequently, stretch activation of p38 MAPK, which was previously shown dependent on the activation of TACE-mediated TNFa release (Zhan et al, 2007), was abolished by PP2 (Fig. 1E).…”
Section: Src Mediates Mechanical Activation Of Tace In Myoblastssupporting
confidence: 65%
See 3 more Smart Citations
“…1D). Consequently, stretch activation of p38 MAPK, which was previously shown dependent on the activation of TACE-mediated TNFa release (Zhan et al, 2007), was abolished by PP2 (Fig. 1E).…”
Section: Src Mediates Mechanical Activation Of Tace In Myoblastssupporting
confidence: 65%
“…We previously showed that mechanical stretch of myoblasts rapidly activates TACE (Zhan et al, 2007). To assess whether Src mediates TACE activation by mechanical stretch, we first investigated whether there is a causal relationship between Src activity and TACE phosphorylation and activation in mechanically stretched myoblasts.…”
Section: Src Mediates Mechanical Activation Of Tace In Myoblastsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also established that TNFα stimulates differentiation of muscle precursor cells 14,15 by activating the mitogen-activated protein kinase p38. 15,16 Expectedly, we found that PrP-KO muscles displayed significantly reduced amounts of active [phosphorylated (P-)] p38 than WT samples. P-p38 regulates muscle differentiation in multiple ways; it directly activates pioneer muscle regulatory factors (MRFs), such as MyoD and Myf5, but it also regulates the ATP-dependent SWI/SNF chromatin remodeling complex that allows access and binding of muscle transcription factors (MEF-2 and MRFs) to their specific loci.…”
Section: The Prion Protein In Pathology and Physiologymentioning
confidence: 69%